Genetic variability and selective breeding for traits of aquacultural interest in the Pacific oyster (Crassostrea gigas) (slides) - Boudry, Pierre; Degremont, Lionel; Taris, Nicolas; Mccombie, Helen; Haffray, Pierrick; Ernande, Bruno (Aquaculture Biotechnology Workshop, 2004)
To date, the most significant genetic improvement for the production of Pacific oyster (Crassostrea gigas) has been obtained through the breeding of triploids, especially since the development of tetraploids. Quantitative genetics studies suggest that significant gains, for disease resistance or for other traits of aquacultural interest, could be obtained in diploids using this approach. However, the limited extent of hatchery-propagation (versus natural recruitment) and/or various technical difficulties and biological characteristics of the species have retarded the development of selective breeding programs. Recently, in the U.S.A., Australia and New Zealand, countries where hatcheries are a major source of C. gigas juveniles, family-based selective breeding programs have been initiated to improve growth and yield. In Europe, where both natural and hatchery-propagated spat are farmed, no large scale selective breeding programs have yet been initiated. However, special attention has been paid to "summer mortalities", for which the causal factors are still unclear. Our studies have shown that family-based selective breeding can improve spat survival, with no impact on growth. However, a genetic trade-off between survival and reproductive allocation was shown in adults, but was influenced by environmental variation. This might explain how additive genetic variance for fitness-related traits is maintained in wild populations. Practical difficulties in breeding large numbers of families are a major constraint for family-based selective breeding in oysters. We have shown that genetic variability exists for several larval traits, which increases the imbalance in reproductive success between breeders in hatchery-propagated populations. Multiplexed-microsatellite markers can be efficiently used to trace parentage in mixed-family breeding programs. Finally, a means of introgression of traits of interest from genetically improved diploids to polyploids will allow the combination of selective breeding and polyploidization.